On decompositions of affine Coxeter groups in semi-direct products - Jushenko, E. (Algebra and Discrete Mathematics, 2004)
In this paper we study affine Coxeter groups. We
show how to construct decompositions of the investigated groups
into semi-direct products. We use this to give the complete list of
irreducible representations of affine Coxeter groups.